(untitled) (MAUSAM, 1984)
A case of formation of a cyclonic storm in the Bay of Bengal and some cases of intensification of equatorial trough during pre-monsoon period were studied with the help of GOES-l satellite wind flow data, It could be inferred that divergence in these cases was mostly generated and the development took place without the movement of any pre-existing divergent system aloft, Onset of the southwest monsoon along the west coast, together with formation of a cyclonic storm in the Arabian Sea and three other cases of formation of depression in the Bay of Bengal were examined in light of the above wind flow data, The development of these systems took place in the presence of upper air divergence systems.